Aging mulberry trees (Morus nigra L): The Charterhouse, London, UK. Issue 3 (3rd July 2022) - Lageard, Jonathan G. A.
ABSTRACT: Black or Common Mulberry ( Morus nigra ) was introduced into Britain in the late sixteenth – early seventeenth centuries and has since had limited success as an ornamental and fruit-producing tree. Older specimens survive in a limited number of locations including at The Charterhouse in central London. Four of these trees were investigated with the aid of standard dendrochronological techniques, historic images, including an early postcard and a painting by Edward Ardizzone, and with the application of expert knowledge of the forms and ages of contemporary mulberry trees. Results included the creation of a new ring-width chronology (CH_Mulberry) and dating that suggests the two oldest trees may well have been planted to commemorate either Queen Victoria's Golden (AD 1887) or Diamond Jubilee (AD 1897). The research represents a first known dendrochronological investigation of the species, highlighting issues associated with sampling "tortuous" growth forms and the poor visibility of sapwood rings, as well as the potential for the use of branch ring-widths to facilitate dendrochronological dating of fruit and other trees.